UJI AKTIVITAS EKSTRAK ETANOLIK DAUN JATI (Tectona grandis L. f.) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI SECARA INVITRO - HF, Fildza; M.A., Rindya; -, Masfiyah; W, Rina (Media Farmasi Indonesia, 2017)
ABSTRACT Indonesia is a country which has a plant biodiversity, one of them is teak (Tectona grandis L.f.). Teak leaf had has flavonoids, saponins, tannin, quinones, and steroids/triterpenoids compound which have antibacterial activity. Aim of this study to determine the activities of teak leaf ethanol extract on bacteria’s growth. The type of the research was experimental post test only control group design. There are two bacteria group, S. aureus andS. epidermidis. The treatment performed with absorbs the extract into a disc then place it over Mueller-Hinton agar which had been incubate for 24 hours with S. aureus and S. epidermidis cultures. The concentration of extract was 6,25%, 12,5%, and 25%. Clear zone was measured by calliper. Data were analyzed using One Way ANOVA and continued with Post Hoc test. The result showed that data was distributed normally and homogeny. The highest clear zone average was obtained on S. epidermidis which has 25% extract concentrate group, and the lowest was S. aureus which has 6,25% extract concentrate group. One Way ANOVA analyze showed the value p<0,05. It concluded, that teak leaf has an activity to inhibit bacteria’s growth, but the activity was higher on Staphylococcus epidermidis.